2021
DOI: 10.3390/jcm10030469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microcirculatory Perfusion in Obese and Non-Obese Patients Undergoing Cardiac Surgery with Cardiopulmonary Bypass

Abstract: Obesity is a frequent comorbidity among patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). Cardiac surgery with CPB impairs microcirculatory perfusion, which is associated with multiple organ failure. As microvascular function is frequently compromised in obese patients, we studied whether cardiac surgery with CPB has a more detrimental effect on microcirculatory perfusion in obese patients. Sublingual microcirculatory perfusion was measured with sidestream dark field (SDF) imaging in obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…There are conflicting reports concerning the influence of CPB on MFI. Some studies have reported that MFI increased compared with the baseline after the start of CPB during surgery ( 18 , 21 ), while some did not observe this effect during cardiac surgery ( 20 , 22 , 23 ), and others reported that MFI significantly decreased compared with the baseline during ICU follow-up ( 24 , 25 ). It is speculated that the current measurement method of MFI only reflects the abnormal flow of slow microcirculation and does not consider the abnormal flow of hyperdynamic microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports concerning the influence of CPB on MFI. Some studies have reported that MFI increased compared with the baseline after the start of CPB during surgery ( 18 , 21 ), while some did not observe this effect during cardiac surgery ( 20 , 22 , 23 ), and others reported that MFI significantly decreased compared with the baseline during ICU follow-up ( 24 , 25 ). It is speculated that the current measurement method of MFI only reflects the abnormal flow of slow microcirculation and does not consider the abnormal flow of hyperdynamic microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Una serie de estudios han establecido que la obesidad también se asocia con cambios en la función vascular dentro del TA, ya que produce alteraciones en los capilares tisulares, lo que conduce a hipoxia localizada. 18,19 No obstante, un informe demostró que los sujetos obesos tienen aumento en lugar de disminución de la tensión de oxígeno dentro del TA, a pesar de la reducción del flujo sanguíneo. 20 Se debe señalar que este último estudio no descarta la posibilidad de zonas de hipoxia localizadas.…”
Section: G E N E R a L I Da D E S D E L A S A D I P O C I Na Sunclassified
“…Diversos hallazgos coinciden en que la disminución de la cantidad y la alteración de la función de los capilares dentro del TA puede limitar el aporte de nutrientes y contribuir a la insulinorresistencia. 18 En forma alternativa, esta disfunción vascular podría contribuir a la inflamación, provocando necrosis y muerte de los adipocitos inducida por isquemia, seguida por inclusión y activación de los macrófagos.…”
Section: G E N E R a L I Da D E S D E L A S A D I P O C I Na Sunclassified
“…Testicular microcirculation disorders are not uncommon in clinical practice, most commonly in varicocele ( 7 ), but also in chronic diseases that cause systemic microcirculation disorders. The relationship between microcirculation disorders and chronic diseases has been a hot topic of ongoing research ( 8 , 9 ), and the relationship between microcirculation disorders and testicular spermatogenesis is an area of ongoing interest to urologists, but research into testicular microcirculation is still in an exploratory phase due to the specific anatomy of the testis and the limitations of technology. It has been reported that better-quality sperm tend to be found in areas of the testis with more abundant blood perfusion ( 10 ).…”
Section: Introductionmentioning
confidence: 99%